Agricultural index insurance for development - Jensen, Nathaniel D.; Barrett, Christopher B. (Wiley, 2017)
Index insurance is often promoted as a solution to many of the barriers that are thought to limit the supply of formal insurance coverage to smallholder farmers and livestock owners in developing countries. This manuscript summarizes the state of index insurance, paying special attention to the key challenges facing index insurance if it is to become a more effective tool for development. We then offer recommendations to tackle those challenges by strategically investing in a set of public goods and services geared towards addressing key informational gaps and improving the quality of index insurance products around the world.